(untitled) (Editora Impacto Científico, 2025)
This research, conducted by Oliveira (2024), titled Teachers’ Perceptions of the Educational Impacts Caused by the COVID-19 Pandemic on Students of the Technical Agricultural Course at a Federal Institute in Northern Minas Gerais, investigated the effects of the pandemic on technical education in a rural context. Employing a mixed-methods approach, with structured questionnaires applied to 60 teachers from the Federal Institute of Northern Minas Gerais in Salinas, the study identified challenges such as the lack of technological infrastructure, difficulties in student motivation, negative impacts on mental health, and increased inequalities in access to education. The findings, presented in Tables 1 to 9, highlight the need for continuous training in educational technologies, pedagogical strategies adapted to remote and hybrid teaching, and expanded emotional support for students and teachers. The pandemic exacerbated pre-existing inequalities, underscoring the importance of public policies to promote educational equity. The research emphasizes the relevance of in-person practices in technical agricultural education and proposes recommendations to strengthen educational resilience in crisis scenarios.